2022
DOI: 10.1177/10732748211045276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Frailty on Treatment Outcome in Nongeriatric Patients With Head and Neck Cancer and Esophageal Cancer Undergoing Curative-Intent Concurrent Chemoradiotherapy

Abstract: Background Whether the prevalence of frailty and its clinical significance are relevant to treatment outcomes in younger (aged < 65 years) cancer patients remains uncertain. This study aimed to evaluate the impact of frailty on treatment outcomes in younger cancer patients with head and neck and esophageal malignancy. Material and methods This multicenter prospective study recruited 502 patients with locally advanced head and neck and esophageal cancer during 2016–2017 in Taiwan, aged 20–64 years who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…The incidence of frailty among patients undergoing head and neck oncologic surgery within this meta‐analysis was 8.8% (15953/189059). These results are lower than those observed in previous oncological studies, including those within the field of head and neck care 21,55 . It is difficult to identify an explanation for this finding however, the inherent risks of selection biases must be considered, particularly as fitter (or “less‐frail”) patients have increased candidacy for surgery within the large retrospective studies included in this study.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The incidence of frailty among patients undergoing head and neck oncologic surgery within this meta‐analysis was 8.8% (15953/189059). These results are lower than those observed in previous oncological studies, including those within the field of head and neck care 21,55 . It is difficult to identify an explanation for this finding however, the inherent risks of selection biases must be considered, particularly as fitter (or “less‐frail”) patients have increased candidacy for surgery within the large retrospective studies included in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…These results are lower than those observed in previous oncological studies, including those within the field of head and neck care. 21,55 It is difficult to identify an explanation for this finding however, the inherent risks of selection biases must be considered, particularly as fitter (or "less-frail") patients have increased candidacy for surgery within the large retrospective studies included in this study. Other socioeconomic factors such as lower education level, smoking and lower income levels have also demonstrated an association with frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the head and neck cancer population, studies have shown that patients undergoing concurrent chemoradiotherapy experience a high symptom burden in addition to financial toxicity [ 15 ]. Increased age, baseline frailty, concurrent chemoradiotherapy, the presence of comorbidities, and low socioeconomic status have been identified as risk factors for acute care utilization, including emergency department visits and hospital admission [ 16 , 17 , 18 , 19 , 20 , 21 ]. These results are corroborated by studies in patients with glioblastoma, which also demonstrated an association between acute care utilization and age, Karnofsky Performance Status (KPS), and concurrent chemoradiotherapy [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an illustration, among 502 patients aged 24 to 60 years who underwent concurrent chemoradiation for locally advanced head and neck cancer, 33.7% were frail. Those patients had a significantly higher rate of hospitalization, emergency room visits, and treatment incompletion compared to the fit ones [ 6 ]. Thus, it is not surprising that among older patients who are deemed fit enough to undergo concurrent chemoradiation for locally advanced disease, high rates of treatment discontinuation, grade 3–4 toxicity and poor survival have been reported [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%